1996
DOI: 10.1073/pnas.93.1.336
|View full text |Cite
|
Sign up to set email alerts
|

Control of cell division in Escherichia coli: regulation of transcription of ftsQA involves both rpoS and SdiA-mediated autoinduction.

Abstract: The conditioning of culture medium by the production of growth-regulatory substances is a wellestablished phenomenon with eukaryotic cells. It has recently been shown that many prokaryotes are also capable of modulating growth, and in some cases sensing cell density, by production of extracellular signaling molecules, thereby allowing single celled prokaryotes to function in some respects as multicellular organisms. As Escherichia coli shifts from exponential growth to stationary growth, many changes occur, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
155
3
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(162 citation statements)
references
References 46 publications
3
155
3
1
Order By: Relevance
“…The 'stationary phase' sigma factor RpoS stimulates transcription from pQ1 (Sitnikov et al, 1996;M. Ballesteros, S. Kusano, A. Ishihama and M. Vicente, personal communication) and RpoS synthesis is stimulated by high ppGpp levels (Gentry et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The 'stationary phase' sigma factor RpoS stimulates transcription from pQ1 (Sitnikov et al, 1996;M. Ballesteros, S. Kusano, A. Ishihama and M. Vicente, personal communication) and RpoS synthesis is stimulated by high ppGpp levels (Gentry et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The apparent role of a PBP in stationaryphase survival of M. smegmatis is consistent with the dynamic nature of stationary-phase cultures and the appearance of new variants, which presumably requires growth and cell division (Smeulders et al, 1999). Several genes, including bolA and ftsQAZ (Ballesteros et al, 1998, Bohannon et al, 1991Sitnikov et al, 1996), that are involved in the determination of cell shape and structure in E. coli are regulated by the stationary-phase sigma factor RpoS. It has recently been shown that E. coli strains lacking both PBP3 and RpoS have a stationary-phase survival defect similar to the defect in surA rpoS double mutants.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that supernatant fluid from stationaryphase batch cultures, which should contain quorum-sensing signal molecules, had little or no effect on rpoS : : lacZ transcriptional and translational fusions (Garcia-Lara et al, 1996;Sitnikov et al, 1996;Hengge-Aronis, 2002). Furthermore, intracellular RpoS concentrations, as well as rpoS mRNA levels, did not increase in parallel with cell density in fed-batch culture (Teich et al, 1999;Yoon et al, 2003).…”
Section: Discussionmentioning
confidence: 99%